2013
DOI: 10.1245/s10434-013-3213-1
|View full text |Cite
|
Sign up to set email alerts
|

Intraperitoneal Chemotherapy of Peritoneal Carcinomatosis Using Pressurized Aerosol as an Alternative to Liquid Solution: First Evidence for Efficacy

Abstract: BackgroundPeritoneal carcinomatosis (PC) is an unmet medical need. Despite recent improvements, systemic chemotherapy has limited efficacy. We report the first application of intraperitoneal chemotherapy as a pressurized aerosol in human patients. MethodsThree end-stage patients with advanced PC from gastric, appendiceal, and ovarian origin were treated as a compassionate therapy. All patients had received previous systemic chemotherapy. A pressurized aerosol of CO2 loaded with doxorubicin 1.5 mg/m2 and cispla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
297
2
20

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 318 publications
(321 citation statements)
references
References 18 publications
2
297
2
20
Order By: Relevance
“…The aerosol form accomplishes homogeneous drug distribution [30], while it is believed that the high intra-abdominal pressure enhances tissue penetration and antitumor effects [31,32]. As a consequence, a low dose of chemotherapy can be used, causing low systemic drug uptake and toxicity [29,33]. Interestingly, Solass and coworkers indeed showed that clinical PIPAC therapy with Doxorubicin achieves high tissue drug concentrations, even though a relatively low dose is nebulized [29].…”
Section: Current Clinical Management Of Pcmentioning
confidence: 99%
See 1 more Smart Citation
“…The aerosol form accomplishes homogeneous drug distribution [30], while it is believed that the high intra-abdominal pressure enhances tissue penetration and antitumor effects [31,32]. As a consequence, a low dose of chemotherapy can be used, causing low systemic drug uptake and toxicity [29,33]. Interestingly, Solass and coworkers indeed showed that clinical PIPAC therapy with Doxorubicin achieves high tissue drug concentrations, even though a relatively low dose is nebulized [29].…”
Section: Current Clinical Management Of Pcmentioning
confidence: 99%
“…As a consequence, a low dose of chemotherapy can be used, causing low systemic drug uptake and toxicity [29,33]. Interestingly, Solass and coworkers indeed showed that clinical PIPAC therapy with Doxorubicin achieves high tissue drug concentrations, even though a relatively low dose is nebulized [29].…”
Section: Current Clinical Management Of Pcmentioning
confidence: 99%
“…Application of the therapeutic aerosol was performed as described previously [1]. Shortly, 30 mL of a saline solution stained with methylene blue 0.0003 % were aerosolized with a nebulizer (Capnopen ® , Capnomed, Villingendorf, Germany) at a pressure of 15 mmHg and room temperature (24.5°C) and maintained for 15 min.…”
Section: Application Of Therapeutic Aerosolmentioning
confidence: 99%
“…Pressurized IntraPeritoneal Aerosol Chemotherapy (PIPAC) has received much attention in recent years due to its superior pharmacological properties, which offers potential clinical advantages [1]. In particular, locoregional administration of a therapeutic substance as an aerosol under pressure allows higher tissue penetration, optimal exposition of the surface of the target organ to the drug, dose reduction and low systemic exposure.…”
Section: Introductionmentioning
confidence: 99%
“…Compared with conventional IPC using catheters or to Hyperthermic IntraPeritoneal Chemotherapy (HIPEC), PIPAC achieves a more homogeneous distribution of the drug onto the exposed peritoneal surfaces [5]. Moreover, PIPAC increases drug penetration into the peritoneal tissue by application of an artificial hydrostatic intraperitoneal pressure [6,7].…”
Section: Introductionmentioning
confidence: 99%